Redes transatlánticas Intelectuales y artistas entre América Latina y Europa durante la Guerra Fría - Abrego, Verónica; Bremer, Thomas (Bibliotheca Ibero-Americana, 2023)
The Cold War founded a bipolar political order and generated a form of dichotomous thinking, placing the world under the constant threat of nuclear catastrophe. Although it divided Europe, it was nevertheless in the then so-called Third World where the conflict claimed its numerous victims, many of them in Latin America. The cultural field was also the scene of the superpower struggles for hegemony, leaving its mark on the intense intertwining between Latin America and Europe.Although the bipolar context is essential to understand the developments of almost five decades, there is still little research that investigates the circumstances and consequences of the conflict for the cultural agents who have historically shaped the common cultural space on both sides of the Atlantic.This volume brings together case studies that critically explore various aspects of that long conflict from a transatlantic research geography. From the perspectives of literary and gender studies, musicology, global history and art ory, the works configure an interdisciplinary panorama of the dynamics of the formation of intellectual and artistic networks, of action and solidarity, and of materialization of geographic nodes. Protagonists, associations, institutions and their networks allow us to explore intellectual and artistic positions, reconstruct the bipolar order broken down to the phenomena of personal and daily cultural life, and also those spaces of a certain autonomy not limited to the logic of the political orders of the superpowers